Jesucristo superestrella - Carter, Glenn; Symonds, Dusty; Pradon, Jerome, 1964-; Castle, Renee; Mayall, Rik; Edwards, Gale; Rice, Tim, 1944-; Morris, Nick; Johanson, Fred; Lloyd Webber, Andrew, 1948-; Knowland, Nicolas D.; Kirk, Roger; et al. (Universal, 2001)
Interpretación musical de la historia de las últimas semanas de Cristo.